2014
DOI: 10.1590/s0100-736x2014000200016
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre a biometria ultrassonográfica ocular e os parâmetros morfométricos do crânio, idade, peso e gênero em gatos domésticos

Abstract: Pesq. Vet. Bras. 34(2):192-198, fevereiro 2014 192 RESUMO.-O exame ultrassonográfico ocular é indispensá-vel no pré-operatório de procedimentos cirúrgicos intraoculares como a facectomia, além de ser uma ferramenta complementar ao exame oftalmológico, em casos de perda da transparência dos meios ópticos. A inexistência de estudos acerca de padrões de normalidades para as medidas do bulbo ocular e de suas estruturas internas nos gatos, cujos valores possibilitam o monitoramento de enfermidades e auxiliam e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…among the evaluated animals, corroborating the results of studies performed in humans (Larsen, 1979) and animals (Assadnassab & Fartashvand, 2013;Bapodra et al, 2010;Beserra et al, 2009;Ekesten & Torrång, 1995;Ferreira et al, 2014;Gonçalves et al, 2009;Kassab, 2012;McMullen & Gilger, 2006;Mirshahi et al, 2014;Montiani-Ferreira et al, 2008;Plummer et al, 2003;Potter et al, 2008;Rajaei et al, 2016;Ribeiro et al, 2009;Ruiz et al, 2015;Silva et al, 2010;Squarzoni, 2011;Toni et al, 2010Toni et al, , 2013Tuntivanich et al, 2007). In addition, no differences were found between the horizontal and vertical planes, corroborating the results of studies that used both planes to perform biometric measurements (Bapodra et al, 2010;Mirshahi et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…among the evaluated animals, corroborating the results of studies performed in humans (Larsen, 1979) and animals (Assadnassab & Fartashvand, 2013;Bapodra et al, 2010;Beserra et al, 2009;Ekesten & Torrång, 1995;Ferreira et al, 2014;Gonçalves et al, 2009;Kassab, 2012;McMullen & Gilger, 2006;Mirshahi et al, 2014;Montiani-Ferreira et al, 2008;Plummer et al, 2003;Potter et al, 2008;Rajaei et al, 2016;Ribeiro et al, 2009;Ruiz et al, 2015;Silva et al, 2010;Squarzoni, 2011;Toni et al, 2010Toni et al, , 2013Tuntivanich et al, 2007). In addition, no differences were found between the horizontal and vertical planes, corroborating the results of studies that used both planes to perform biometric measurements (Bapodra et al, 2010;Mirshahi et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…The present study was conducted with Jersey cattle, which were chosen for their phenotypic homogeneity, in addition to being considered remarkable animals for milk production, feed conversion, precocity, Ocular structures such as the cornea, anterior chamber, anterior and posterior lens capsules, vitreous chamber and posterior wall presented similar echogenicity and echotexture to those of other mammals (Assadnassab & Fartashvand, 2013;Beserra et al, 2009;Ekesten & Torrång, 1995;Ferreira et al, 2014;Gonçalves et al, 2009;Kassab, 2012;Laus et al, 2013;McMullen & Gilger, 2006;Mirshahi et al, 2014;Plummer et al, 2003;Potter et al, 2008;Ribeiro et al, 2009; Silva et al, 2010; Squarzoni, 2011; Toni et al, 2013;Tuntivanich et al, 2007) and wild animals (Bapodra et al, 2010;Harris et al, 2008;Hernández-Guerra et al, 2007;Montiani-Ferreira et al, 2008;Rajaei et al, 2016;Ruiz et al, 2015;Squarzoni et al, 2010;Toni et al, 2010). The iris and the ciliary body in the studied cattle were thick and irregular when compared to those of other species such as dogs (Squarzoni, 2011) and humans (Lorente-Ramos et al, 2012;Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferreira et al (2014) demonstrated the inefficiency of frequencies between 8 and 9MHz when measuring cornea thickness in adult cats. Transductors with frequency higher than 20MHz give greater image definition and penetration power (from 20 to 80μm), allowing the visualization and measurement of images of the anterior eye segment, including the cornea in dogs and cats (Bentley et al 2003).…”
Section: Discussionmentioning
confidence: 99%